The coordinated control strategy for isolated DC microgrid based on adaptive storage adjustment without communication. (15th October 2019) - Mi, Yang; Chen, Xin; Ji, Hongpeng; Ji, Liang; Fu, Yang; Wang, Chengshan; Wang, Jianhui
Highlights: Typical configuration and four operation modes of DC Microgrid. Power sharing control in hierarchical control for energy storage units. Power balance control in hierarchical control for balance state of charge. Virtual inertia control for power generation and Load Side Control for load consumption. The autonomous operation of isolated DC microgrid can be realized without communication. Abstract: In the DC microgrid, renewable energy sources are increasingly applied as distributed generations to replace the traditional energy at remote locations. Meanwhile, energy storage system needs to be employed to maintain the balance between fluctuated power generation and load consumption. In this paper, the coordinated control strategy is proposed for the stability operation of isolated DC microgrid. In order to avoid over-charging or deep-discharging for certain energy storage units, the novel hierarchical droop control scheme is introduced to balance state of charge among energy storage units to. Additionally, the virtual inertia control is designed to adjust the output power of renewable energy generation, and the fuzzy iterative method is added to reduce the voltage deviation induced by droop control. According to the bus voltage variation and the preset value of threshold, the load side control is constructed to guarantee the stability operation of high-priority loads. Finally, the autonomous operation of isolated DC microgrid can be realized without relying on communication. Comprehensive cases based on real-time digital simulator are provided to demonstrate the effectiveness of the proposed control strategy.